The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1292/jvms.60.799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 7.2% Hypertonic Saline Solution Infusion on Arterial Blood Pressure, Serum Sodium Concentration and Osmotic Pressure in Normovolemic Heifers.

Abstract: ABSTRACT. The effects of an intravenous (iv) infusion of a small volume (5 ml/kg) or large volume (15 ml/kg) of hypertonic saline solution (HSS; 7.2%, 2,400 mOsmol/kg·H 2 O) and those of an iv infusion of 5 ml/kg isotonic saline solution (ISS; 300 mOsmol/kg·H 2 O) on plasma volume, arterial blood pressure, serum sodium concentrations and osmotic pressure were investigated in conscious heifers. Nine heifers (3 heifers/group) were monitored for 120 min after the initiation of fluid replacement. The relative plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A previous study of heifers [20] demonstrated that a large volume of HSS infusion induced decreases in PaO 2 accompanied by an accelerating HR. This pulmonary response, therefore, may be caused by a decrease in pulmonary circulation.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A previous study of heifers [20] demonstrated that a large volume of HSS infusion induced decreases in PaO 2 accompanied by an accelerating HR. This pulmonary response, therefore, may be caused by a decrease in pulmonary circulation.…”
Section: Discussionmentioning
confidence: 92%
“…It was reported that transient decreases in the SAP of heifers given 5 ml/kg-HSS occurred immediately the start of the after HSS infusion [20]. Although arterial blood pressure was decreased at the immediately after the HSS infusion, there are many reports that the use of HSS has successfully restored cardiovascular function, especially arterial blood pressure, in dogs and cats with hemorrhagic or hypovolemic shock [5, 6, 9-11, 14, 15, 23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium bicarbonate solution, the alkalizing agent of choice, is most often used as a 7.0% hypertonic solution that is commercially available in Japan. The positive inotropic effect is rapid, usually within 2 to 5 min of infusion of a hypertonic solution, such as 7.2% hypertonic saline and 7.0% hypertonic sodium bicarbonate solutions [2,15]. These responses are produced by increased osmolarity of 30 to 150 mOsmol/l [14].…”
mentioning
confidence: 99%